Deepening Diversity: A Collection of Teaching Perspectives and Strategies from Social Justice Advocates. Issue 1 (4th May 2022) - Fernandez, Mariela; Lee, KangJae Jerry; Larson, Lincoln; Johnson, Corey W.; Mowatt, Rasul; Bush, Kimberly; Robinett, Jeremy; Sharaievska, Iryna; Stewart, William
Abstract: Contemporary population trends impact leisure experiences and service delivery, requiring recreation and leisure departments to prepare students to meet the needs of an increasingly diverse clientele. However, with little formal training on how to teach content concerning diverse populations, this can be a daunting task. The panel session Preparing Students to Serve Diverse Populations was featured at the 2018 The Academy of Leisure Sciences (TALS) Research and Teaching Institute to help instructors navigate the challenges that arise when teaching diversity-related content to undergraduate and graduate students. This paper focuses on the lessons and recommendations that emerged from that panel of social justice scholars. Using the teaching to transgress philosophy and the Teaching Tolerance Anti-bias Framework, we highlight personal philosophies, pedagogical experiences, and specific activities that may help other instructors teach beyond diversity to facilitate students' connections with broader issues of social justice.